Pendampingan Literasi Akademik dan Non Akademik Berbasis Daring Bagi Mahasiswa Baru di Kota Kediri - Titis Thoriquttyas; Nurul Ahsin (Fakultas Ushuluddin, Adab, dan Dakwah, 2022)
In the scope of higher education, one concrete example of the concept for Learning from Home (LFH) is the Introduction to Campus Life for New Students (PKKMB) which is carried out online. Psychologically, new students have a high level of vulnerability to anxiety and worry in starting to understand the learning process in the university. Based on the fact above, the assistant designs community service activities based on mentoring to increase literacy related to campus life for new students who live in Kediri. There were 46 students participating in the activity using google meet media in its implementation. Activities are designed based on research with a focus on two things, namely 1). mapping research on barriers faced by new students; 2) mentoring new students to improve academic and non-academic literacy when entering tertiary level. The findings of mentoring activities, namely, from 46 participants, there were at least four main obstacles and challenges, namely 1) the emergence of anxiety and worry about learning patterns in tertiary institutions (27%); 2) pessimism regarding the sustainability of online learning models (19%); 3) feelings of fear and confusion in following the PKKMB material and insight into the academic / non-academic atmosphere on each campus (46%); 4) concerns about the post-Covid pandemic learning process have subsided and the implementation of offline lectures (8%).